2018
DOI: 10.5433/1679-0359.2018v39n2p511
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange, leaf and root dry mass in Bell Pepper under fertigation with nitrogen and potassium

Abstract: Bell pepper is a vegetable-fruit of great economic importance in Brazil. Crop production demands adequate water supply, nutrients, and light. The objective of this study was to evaluate gas exchange (net photosynthesis, stomatal conductance, transpiration, internal carbon concentration and instantaneous carboxylation efficiency) and dry mass accumulation in leaves and roots under fertigation with nitrogen and potassium. The experiment was conducted in a completely randomized design in a factorial scheme (4 × 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…Therefore, reductions in the photosynthetic and transpiration rates, intracellular CO 2 concentration and stomatal conductance in eggplants submitted to greater nitrogen doses were probably by nutritional excess. Lorenzoni et al (2018) found similar results of nitrogen on sweet pepper (Capsicum annuum L.) plants for the above variables. According to Lorenzoni et al (2018), an excess of nitrogen or an imbalance with other nutrients trigger detrimental effects on plant performance, which may be a result of the physiological imbalance.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Therefore, reductions in the photosynthetic and transpiration rates, intracellular CO 2 concentration and stomatal conductance in eggplants submitted to greater nitrogen doses were probably by nutritional excess. Lorenzoni et al (2018) found similar results of nitrogen on sweet pepper (Capsicum annuum L.) plants for the above variables. According to Lorenzoni et al (2018), an excess of nitrogen or an imbalance with other nutrients trigger detrimental effects on plant performance, which may be a result of the physiological imbalance.…”
Section: Resultssupporting
confidence: 60%
“…Lorenzoni et al (2018) found similar results of nitrogen on sweet pepper (Capsicum annuum L.) plants for the above variables. According to Lorenzoni et al (2018), an excess of nitrogen or an imbalance with other nutrients trigger detrimental effects on plant performance, which may be a result of the physiological imbalance.…”
Section: Resultssupporting
confidence: 60%